FDG avid cerebellar atypical meningioma masquerading as solitary brain metastases in a recently diagnosed breast malignancy: a toss between MR and CT - Shanmuga Sundaram Palaniswamy (SpringerOpen, 2021)
Abstract Background SUV Max is a glycolytic index obtained from PET imaging, relates to tumour cell proliferation. FDG uptake (i.e. SUV max) is found to be high in aggressive tumours and is used to identify malignant from benign pathologies. Meningiomas are intracranial tumours which display varying grades of FDG avidity based on its biological aggressiveness. Benign grade I meningiomas are FDG non-avid, while the rest of the typical and atypical meningiomas show varying degrees of FDG avidity. Uptake of FDG can be high in certain infectious and inflammatory brain etiologies and pose a diagnostic challenge in differentiating benign brain lesions from neoplasms. MRI is the preferred modality for accurately identifying meningiomas, providing superior contrast differentiation and its ability to differentiate extra-axial from intra-axial brain lesions. CT is said to be superior in specific types of meningioma where there is calcification and adjacent changes in calvarium. Although typical meningiomas have characteristic MRI features, care must be taken to avoid misleading diagnosis between brain tumours and atypical meningiomas. Case presentation We are presenting a recently diagnosed case of invasive breast carcinoma (Ca) referred for staging by PET/MR imaging. Based on atypical DWI and ADC map findings, MRI falsely reported an atypical meningioma as a brain metastasis. Abnormal intense FDG uptake was noted in a well-defined homogeneously enhancing mass lesion in posterior fossa in left paramedian aspect and broad base to left transverse sinus protruding into left cerebellar hemisphere. Atypical meningioma Grade III, i.e. papillary meningioma was later histologically proven. Conclusions We wish to highlight the inconsistency of DWI and ADC map MR findings in papillary meningioma masquerading as solitary brain metastases in a Ca breast patient on 18F FDG PET/MR imaging. From an imaging standpoint, it is important to recognize the variable and pleomorphic features exhibited by meningiomas in MR based on atypical location, histological subtypes, and biologic behaviours. Further FDG PET was incremental in displaying a high SUV max indicating biologic aggressiveness of lesion and correlating with the CT diagnosis of papillary meningioma.